Ukrainian adaptation of the Clance Impostor Phenomenon Scale (CIPS) - T. Yablonska; A. Shevchuk (Науковий вісник Мукачівського державного університету. Серія "Педагогіка та психологія")
Expanding the methodological toolkit of research, particularly through adapting foreign psychometric tools, is crucial for Ukrainian psychology. This allows for conducting new research and comparing its results. One promising direction is studying the impostor phenomenon, manifested in an individual’s doubts about their achievements. The Clance Impostor Phenomenon Scale, developed by foreign researchers, is used for this purpose. This study aimed to adapt the Clance Impostor Phenomenon Scale into Ukrainian. The Clance Impostor Phenomenon Scale was translated into Ukrainian by two psychologists using the back-translation method. The research sample consisted of 297 students aged 18 to 22 (M = 20.4, SD = 1.49), including 82 males and 215 females. Descriptive statistics, reliability analysis of scales, correlation analysis (Spearman’s coefficient), and confirmatory factor analysis were used. The results of the study indicate a considerable degree of consistency between the obtained data and the foundational theoretical model. The assessment of content validity revealed a significant number of statistically significant correlations. A high level of test-retest reliability was identified for the adapted methodology. The resulting factor model is conceptually similar to the original; however, it is not identical. Other studies have also noted the emergence of new factor models, suggesting the potential for refinement of this methodology or reflecting age, temporal, and cross-cultural differences among the subjects studied. The evaluation of the psychometric characteristics of the Ukrainian version of the Clance Impostor Phenomenon Scale demonstrated high internal validity and reliability for the adapted tool. The Ukrainian version of the Clance Impostor Phenomenon Scale may be valuable for the psychodiagnosis of impostor syndrome manifestations and further standardisation and application in comparative research. The findings could contribute to optimising psychological support by taking into account the specific characteristics of impostor syndrome in the course of psychological work